Korelasi Penyebab Kemiskinan Dengan Kepedulian Muslim: Analisis Penyebab Dan Akibat Kemiskinan Di Kalangan Ummat Islam - Suaidi Suaidi (Universitas Maritim AMNI Semarang, 2023)
The position of wealth functions to cover basic needs as provisions for carrying out worship to Allah, SWT. Assets in Islamic legal governance function to spread prosperity to the weaker sections of society. Therefore, the weak party's right to ownership of property must be released and distributed to other parties, whether requested or not. Economic inequality is a trigger for crimes committed because of poverty, such as theft. Islam views that poverty is not an insult, but Islam provides solutions to poverty alleviation such as by requiring the payment of zakat and encouraging infaq shodakoh and other forms of obligations which aim to care for the weak, such as waqf. Islam is very concerned about equal distribution of property ownership, in fact its concern is included in the structure of the pillars of Islam, namely the obligation to pay zakat.